Voices Versus Visions: A Commentary on Academic Library Collections and New Directions. Issue 2 (3rd July 2019) - Scherlen, Allan; McAllister, Alex D.
Abstract: Academic library collections are under pressure to follow dominant voices in the library world to redefine library missions and collections according to emerging trends in new library services. These trends call for a shift in focus away from traditional resource support for curriculum and research to new tech-related and other services. This sea-change in academic library function is led by the voices of major figures at library conferences and taken up by some library leaders who want to be on the cutting edge of reevaluating traditional academic library collections and the very essence of the mission of academic libraries. Thus, it is important to question dominant voices at library conferences, in published discourse, and among our colleagues so as to prevent the shaping of all libraries into a common mold of new services that can seem alluring but can potentially disconnect our libraries from their more fundamental role in supporting the research and curriculum of our institutions. Listening to the input of our faculty and student stakeholders, as well as balancing new roles with the value of foundational ones, are key to preserving our central importance to the university.